Histological validation of cardiac 99mTc-DPD uptake in patients with cardiac transthyretin amyloidosis. (3rd October 2022) - Ungericht, M; Groaz, V; Messner, M; Zaruba, M M; Lener, D; Stocker, E; Kroiss, A; Poelzl, G
Abstract: Background: Cardiac transthyretin (ATTR) amyloidosis is a progressive and fatal disease caused by the extracellular deposition of misfolded ATTR protein in the myocardium. In an era where new therapies are rapidly emerging, development of non-invasive imaging modalities to quantify amyloid burden over time is of utmost importance. Although endomyocardial biopsy (EMB) remains the gold standard in amyloid detection and typing, 99mTc-DPD scintigraphy is a widely available and accurate tool for non-invasive diagnosis of cardiac ATTR amyloidosis. However, it remains to be determined whether the degree of cardiac 99mTc-DPD uptake correlates with the histological amyloid infiltration on EMB – thus, justifying 99mTc-DPD scintigraphy as a disease monitoring tool. Aim: This single-centre observational study aimed to compare the extent of histologic amyloid burden on EMB with the quantification of cardiac 99mTc-DPD uptake on scintigraphic planar images and SPECT/CT acquisitions in cardiac ATTR amyloidosis. Methods: 26 patients with cardiac ATTR amyloidosis were enrolled. Patients were included in case of (1) EMB-proven ATTR amyloidosis and (2) availability of 99mTc-DPD scintigraphy (reference activity: 550 MBq). Visual interpretation using the Perugini score, quantitative analysis of cardiac 99mTc-DPD uptake by planar whole-body imaging and SPECT/CT using regions of interest (ROI) were performed, and heart to whole-body ratio (H/WB) was measured. Histological amyloid load was quantified as percentage of the analysed myocardial tissue using Sulfated Alcyan Blue staining and the Fiji-ImageJ programme. Pearson's and Spearman's correlation were used for correlation analysis and assessment of agreement. Results: ATTR patients had a median age of 77 [73–79] years and were predominantly male (85%). An abnormal Perugini score (i.e. 2 or 3) was present in 25 patients (96%), whereas 1 patient was assigned Perugini score 1 (4%). Increased cardiac tracer uptake was documented in all patients, both on 99mTc-DPD planar scintigraphy (ROImean 129±37) and SPECT/CT (ROImean 369±142). Histologic amyloid burden on EMB was 32±19% on average. It significantly correlated with Perugini score (r=0.56 p=0.003), as well as with cardiac 99mTc-DPD uptake (planar: r=0.54 p=0.006, SPECT/CT: r=0.48 p=0.018) and H/WB (r=0.41 p=0.046). Conclusion: We have demonstrated a good correlation between histological amyloid infiltration on EMB and cardiac 99mTc-DPD uptake on scintigraphic planar images and SPECT/CT scans, illustrating the potential of 99mTc-DPD scintigraphy to yield reliable quantitative information on cardiac amyloid burden. Further investigations with a larger number of patients are needed to confirm our findings and to implement thresholds in cardiac 99mTc-DPD uptake for being used for guiding disease and therapy management. Funding Acknowledgement: Type of funding sources: None.